MODERN OPPORTUNITIES OF INTERFERON THERAPY AT INFLUENZA AND ACUTE RESPIRATORY INFECTIONS IN CHILDREN - T. A. Chebotareva; A. L. Zaplatnikov; I. N. Zakharova; E. N. Vyzhlova (LLC "Diagnostics and Vaccines", 2015)
The new dosing scheme for the preparation VIFERON®, rectal suppositories for infants of II, III and IV groups of health was suggested. The application of the scheme has resulted in a more pronounced clinical and immunological effects at treatment of influenza and acute respiratory infections compared to the previously used sc heme.